2013
DOI: 10.4161/cc.25415
|View full text |Cite
|
Sign up to set email alerts
|

Identification of p130Cas/ErbB2-dependent invasive signatures in transformed mammary epithelial cells

Abstract: Understanding transcriptional changes during cancer progression is of crucial importance to develop new and more efficacious diagnostic and therapeutic approaches. It is well known that erbB2 is overexpressed in about 25% of human invasive breast cancers. We have previously demonstrated that p130Cas overexpression synergizes with erbB2 in mammary cell transformation and promotes erbB2-dependent invasion in 3-dimensional (3D) cultures of human mammary epithelial cells. Here, by comparing coding and non-coding g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…Our current finding that Smad7 and Smurf2 protein levels are simultaneously and directly suppressed by overexpressed miR424-503 cluster in metastatic breast cancer cells without alterations in their mRNA levels, therefore, represents a novel posttranscriptional model for a coordinated regulation of these 2 factors. Although miRNAs have been reported to target Smad7 (36,37), and miR424 or miR503 overexpression has been separately found to be associated with poor prognosis in breast cancer (38,39), our results provides the first demonstration for miRNA Importantly, this newly identified mode of action is clinically relevant, as shown by our human specimens' data. Thus, a coordinated miRNA modulation of both Smad7 and Smurf2 appears to be an importantly new layer of TGFb signaling in breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 54%
“…Our current finding that Smad7 and Smurf2 protein levels are simultaneously and directly suppressed by overexpressed miR424-503 cluster in metastatic breast cancer cells without alterations in their mRNA levels, therefore, represents a novel posttranscriptional model for a coordinated regulation of these 2 factors. Although miRNAs have been reported to target Smad7 (36,37), and miR424 or miR503 overexpression has been separately found to be associated with poor prognosis in breast cancer (38,39), our results provides the first demonstration for miRNA Importantly, this newly identified mode of action is clinically relevant, as shown by our human specimens' data. Thus, a coordinated miRNA modulation of both Smad7 and Smurf2 appears to be an importantly new layer of TGFb signaling in breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 54%
“…Consistent with this result, 21 years later Pincini et al (2013) [50] showed that ITPKA belongs to the invasive signature of p130Cas/ErbB2 transformed MCF10A.B2 breast cancer cells. In addition to ErbB2, also the v-scr oncogene seems to be sufficient to induce expression of ITPKA.…”
Section: Regulation Of Itpka Expression In Tumor Cellsmentioning
confidence: 59%
“…It was therefore decided that we evaluate the possible interactions of miR-23b in this context, as it has previously been demonstrated to be downmodulated in invasive acini 4 , and that Blimp1 was predicted to be one of its putative targets (TargetScan v. 6.2).…”
Section: Resultsmentioning
confidence: 99%